Management of B ile Duct Injury after Laparoscopic Cholecystectomy (Medicine Today, 2018)
Bile duct injury is one of a life threatening complication of laparoscopic cholecystectomy. It is a disaster for both patient and surgeon because of the associated morbidity, prolonged hospitalization and mortality. The complication can be minimized by early diagnosis and treatment. Minor injury can be managed by conservative treatment. Bile in drainage tube is diagnostic. Minimum bile leakage automatically sealed provided the natural passage remain patent. Further bile leakage can be reduced by stenting the common bile duct by ERCP. Major bile duct injury needs early diagnosis, categorization of level of injury, control of sepsis and some form of surgical intervention. Early referral to tertiary level hospital under experienced hepatobiliary surgeon will give the good result.Medicine Today 2018 Vol.30(2): 95-97